The Scholarly Output of Universities and Academics in the Asia-Pacific Region Who Publish in Major Finance Journals: 2000-2007 - Elvis Jarnecic; Reuben Segara; Lydia Segara; Joakim P. Westerholm (Australasian Accounting, Business and Finance Journal, 2008)
The study examines the scholarly output of all universities and their finance academics in the Asia-Pacific region. We evaluate the scholarly output of 1,341 research academic staff across 300 leading Asia-Pacific universities in the period 2000 to 2007. A significant contribution of our study is that it presents ranking league tables for finance journals with respect to journal quality. The necessity of well defined ranking tables help university executive management, government policy and funding bodies in better assessing research performance. The study also constructs a new measure called to Research Productivity Dependency (RPD) index, which acts as a risk management mechanism to aid universities better assess their reliance on key individual research productive academics.
Keywords: Rankings; Research; Finance; Asia-Pacific Universities